2014
DOI: 10.1172/jci72270
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy: from models to man

Abstract: As recently as 2002, most cases of primary membranous nephropathy (MN), a relatively common cause of nephrotic syndrome in adults, were considered idiopathic. We now recognize that MN is an organ-specific autoimmune disease in which circulating autoantibodies bind to an intrinsic antigen on glomerular podocytes and form deposits of immune complexes in situ in the glomerular capillary walls. Here we define the clinical and pathological features of MN and describe the experimental models that enabled the discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 85 publications
(89 reference statements)
4
138
0
3
Order By: Relevance
“…These immune-complexes for deposits in patients with HBV-GN [19, 20]. Subepithelial immune deposits initiate activation of the complement system of the C3 component, conversion of C5, and subsequent formation of the C5b-9 complex in podocyte membranes [19, 21]. The membrane attack complex (C5b-9) leads to podocyte injury, including calcium influx, oxidative injury, production of arachidonic acid metabolites, cell cycle dysregulation, and endoplasmic reticulum stress [21, 22], These lead to podocyte apoptosis, reduced podocyte adhesion, and detachment of podocytes from GBM, which may result in proteinuria and renal failure [19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…These immune-complexes for deposits in patients with HBV-GN [19, 20]. Subepithelial immune deposits initiate activation of the complement system of the C3 component, conversion of C5, and subsequent formation of the C5b-9 complex in podocyte membranes [19, 21]. The membrane attack complex (C5b-9) leads to podocyte injury, including calcium influx, oxidative injury, production of arachidonic acid metabolites, cell cycle dysregulation, and endoplasmic reticulum stress [21, 22], These lead to podocyte apoptosis, reduced podocyte adhesion, and detachment of podocytes from GBM, which may result in proteinuria and renal failure [19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…She was found to have nephrotic-range proteinuria, which prompted concern for glomerulonephritis secondary to IgG4-RD. A renal biopsy was obtained (Figure 3 & 4) and revealed MGN with positive immunofluorescence stain for PLA2R antibodies, consistent with primary membranous glomerulonephritis, and not consistent with GN secondary to IgG4-RD [7,9]. The patient was started on an angiotensin converting enzyme inhibitor (ACEi) and as needed diuretics with resolution of her lower extremity edema However, there are speculations about potential improvements in the criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of co-existing IgG4-RD and primary MGN exists in the literature, but renal biopsy staining was negative for phospholipase A2 receptor (PLA2R) antibodies [6]. Primary MGN, originally thought to be idiopathic in most cases, is now principally recognized as an organ-specific autoimmune disease, characterized by detection of the PLA2R antibodies [7]. We describe a patient who was diagnosed with IgG4-RD, with subsequent development of lower extremity edema and nephrotic-range proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested a more diverse origin for these cells (56). Characterization of myofibroblasts has identified several signaling pathways enriched or restricted to FOXD1 lineage cells that may permit specificity in developing therapies for fibrogenesis (57,58) Podocytopathy discoveries: specific mechanisms uncover tools for clinical utility Important advances have been made in our understanding of the pathogenetic mechanisms that contribute to the common glomerular diseases IgA nephropathy (IgAN), reviewed by Krzysztof Kiryluk and Jan Novak (59), and idiopathic membranous nephropathy, reviewed by Laurence Beck and David Salant (60). These advances have been informed by studies using animal models and investigations in human populations.…”
Section: Cross-talk Between Infiltrating Leukocytes and Kidney Cellsmentioning
confidence: 99%